A lubricating inorganic fiber reinforced plastic masterbatch and preparation method thereof

Modifying inorganic fibers by nano-two-dimensional sliding sheet-like inorganic material solves the problem of shear damage and dispersion difficulties in plastic reinforcement, and realizes lubricating fluidity, high-strength and high-stiffness plastic masterbatches , suitable for precision injection molding and high strength plastic products.

CN111410791BActive Publication Date: 2024-12-27HAIFENG COUNTY XIAOSHAN PLASTIC IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202010421083.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-05-18
Publication Date
2024-12-27
Estimated Expiration
2040-05-18

AI Technical Summary

Technical Problem

In plastic reinforcement, inorganic fibers with high aspect ratios are easily damaged by screw shear and difficult to disperse, resulting in limited reinforcement effect, and when commonly used lubricants increase, it will affect the stiffness and strength of plastic products.

Method used

The nano-two-dimensional sliding sheet-like inorganic material is modified, and the sliding properties and interface modification effect are used to reduce the amount of lubricant, improve the sliding properties and dispersion of the fibers, reduce screw shear damage, and enhance the flowability of the plastic masterbatches and compatibility.

Benefits of technology

It realizes good sliding and dispersibility of inorganic fibers in plastic products, reduces the negative impact of lubricants on product stiffness and strength, improves the high strength and high stiffness of plastic products, prevents defibrillation, and is suitable for precision injection molding and Plastic products with high strength demand.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111410791B_ABST
    Figure CN111410791B_ABST
Patent Text Reader

Abstract

The invention relates to the field of reinforced plastics, and specifically discloses a lubricating inorganic fiber reinforced plastic masterbatch and a preparation method. First, the adhesion of silica sol is used to adhere and modify inorganic fibers with nanometer two-dimensional sliding flaky inorganic materials, so that the inorganic fibers are given good sliding properties, so that the amount of lubricating additives such as paraffin is reduced during the preparation of the reinforced plastic masterbatch. Further, polystyrene solution is used for infiltration treatment, so that the nanometer two-dimensional sliding flaky inorganic materials are adhered and modified to the inorganic fibers to adsorb polymers at interface defects, which is beneficial for the inorganic fibers to be compatible and dispersed with polymers during the processing, preparation and use of the reinforced plastic masterbatch. The obtained reinforced plastic masterbatch has high strength and high rigidity for injection-molded plastic products, and the surface of the plastic products is smooth, which effectively prevents the problem of fiber removal when used for plastic products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of reinforced plastics, in particular to a reinforced masterbatch of plastics, and in particular to an inorganic fiber reinforced plastic masterbatch with good lubrication and fluidity and a preparation method thereof. Background Art

[0002] As a filler to improve the function of plastics, plastic masterbatch plays an important role in the plastics industry. Plastic raw materials used directly in the processing of plastic products often have many defects. By adding plastic masterbatch with certain functions, plastic products can be given different functions, such as color, antistatic, conductive, flame retardant, reinforced, toughened, wear-resistant, scratch-resistant, rigid, etc. Therefore, various color masterbatches, antistatic masterbatches, conductive masterbatches, flame retardant masterbatches, reinforced masterbatches, rigid masterbatches, wear-resistant masterbatches, etc. are derived.

[0003] In the plastics industry, low-cost inorganic substances such as calcium carbonate were initially prepared into plastic filler masterbatches, which were used in the processing of plastic products to reduce costs. Technicians found that adding a certain amount of calcium carbonate filler masterbatches during the processing of plastic products can not only reduce costs, but also greatly help the rigidity, heat resistance, dimensional stability, etc. of plastics. Therefore, on this basis, various functional plastic masterbatches for functional plastics were developed.

[0004] Reinforced plastics are one of the most widely used varieties in the current plastics industry. There is a huge demand for reinforced plastics in the fields of automobiles, building materials, home appliances, and industry. In the automotive field, such as bumpers; in the building materials field, such as plastic steel doors and windows, PVC pipes for water pipes, HDPE large pipes, corrugated pipes, double-wall corrugated pipes; in the home appliance field, such as refrigerators, TVs and other electrical appliance shells. For this reason, it has become a conventional technology to add a large amount of plastic reinforcement masterbatch in the preparation process of plastics to achieve product reinforcement.

[0005] Plastic reinforcement technology is mainly divided into two major directions: on the one hand, inorganic particles with a particle size of less than 100 nanometers are used to prepare masterbatches. The characteristics of nanomaterials such as small particle size, large specific surface area, high surface energy, and large proportion of surface atoms can be used to greatly improve the impact resistance of plastic products and play a role in strengthening and toughening. However, the effect of nano-enhancement is limited. Since nanomaterials rely on a large number of nano-interfaces to buffer and disperse stress, their toughness is good and the reinforcement is limited. Therefore, it is not suitable for products with high strength requirements. Moreover, due to the difficulty in dispersing inorganic nanomaterials, they are very easy to agglomerate during preparation and use, which will affect the reinforcement effect. Chinese invention patent CN102875869 B discloses a nano-calcium carbonate reinforced toughened plastic masterbatch and its preparation method. The masterbatch is composed of nano-calcium carbonate, micron calcium carbonate, metallocene polyethylene, carrier resin and additives. The blending of nano- and micron calcium carbonate improves the strengthening and toughening effect of the masterbatch. Metallocene polyethylene has high strength and good toughness, which can simultaneously improve the strengthening and toughening effect of the masterbatch. Nano-inorganic powder can be used for plastic reinforcement masterbatch, and its dispersion is the key.

[0006] On the other hand, the most widely used plastic reinforcement is to prepare reinforced plastics by adding various inorganic fibers such as glass fiber, calcium carbonate whisker, calcium sulfate whisker, fiber wollastonite, brucite fiber, carbon fiber, etc. Inorganic fiber reinforced plastics have been widely used. For example, continuous glass fiber and carbon fiber are pre-impregnated with resin and then molded and pressed into shape. They are widely used in reinforced plastic products in the automotive industry, and their reinforcement is significantly improved. However, due to the limitations of product processing, the use of continuous fibers is limited in some small precision reinforced plastics. At present, the most widely used method is to prepare inorganic short fibers into masterbatches and add them directly during the processing of plastic products.

[0007] According to relevant research, the strength improvement of inorganic fibers prepared as masterbatches in plastic reinforcement can exceed 30%. In particular, some inorganic fibers with a larger aspect ratio (aspect ratio greater than 100) have a more obvious reinforcement effect. In the field of functional plastics and engineering plastics, polymer material personnel are constantly improving the application of large aspect ratio inorganic fibers prepared as masterbatches in plastics. Chinese invention patent CN107880522A discloses a whisker-reinforced polyetherketoneketone composite material and its preparation method, using 100 parts of polyetherketoneketone resin, 5 to 30 parts of fusible fluoroplastics, 10 to 50 parts of inorganic whiskers, 0.1 to 5 parts of coupling agents, and 0.1 to 3 parts of cross-linking agents. While maintaining the excellent high temperature resistance, flame retardancy, chemical resistance, and moisture and heat resistance inherent in the polyetherketoneketone resin itself, it can also greatly improve the shear strength and impact strength of the parts, making their wear resistance more excellent. At the same time, it can greatly reduce material costs and meet a wider range of application needs.

[0008] Although inorganic fibers have a significant reinforcing effect on plastics, it is difficult to disperse inorganic fibers with large diameters when used in practice. There are compatibility issues and friction between inorganic fibers and plastic matrices during blending and extrusion granulation, which affects the uniform compatibility between inorganic fibers and plastic matrices. On the one hand, it leads to defibration, which affects the reinforcing effect; on the other hand, when inorganic fibers with large aspect ratios are used to prepare reinforced plastic masterbatches, the fibers are easily sheared by the screw and the aspect ratio is reduced. Although inorganic fiber reinforced plastic masterbatches have good fluidity during processing by adding excessive amounts of paraffin wax, ethylene bis stearamide, etc. to reduce shearing of fibers, however, excessive addition of lubricating modifiers will affect the stiffness of plastic products, resulting in limited reinforcement. Summary of the invention

[0009] At present, inorganic fibers are used as reinforcing materials to prepare reinforced plastic masterbatches. The large aspect ratio inorganic fibers used are easily damaged by screw shearing, and the dispersion of large aspect ratio inorganic fibers is difficult. When a large amount of lubricants such as paraffin are added to disperse the fibers, the rigidity and strength of the plastic products will be adversely affected. In view of this, the present invention proposes a lubricating inorganic fiber reinforced plastic masterbatch and a preparation method. The special feature is that the inorganic fibers are modified by nano two-dimensional sliding flaky inorganic materials to give the inorganic fibers good sliding properties. Further, the nano two-dimensional sliding inorganic materials are combined with the inorganic fibers in an interface modification manner. The inorganic fibers have good sliding properties and dispersibility when sheared and dispersed with the matrix plastic in the screw. The obtained reinforced plastic masterbatch has less lubricating additives and effectively prevents the problem of fiber stripping when used for plastic products. The obtained reinforced plastic masterbatch is suitable for various precision injection molded reinforced plastic products, electrical housings, auto parts, building materials and other plastic products with strength and rigidity requirements.

[0010] In order to achieve the above-mentioned purpose, firstly, a method for preparing a lubricating inorganic fiber reinforced plastic masterbatch is provided, wherein the specific preparation method is as follows:

[0011] S1: dispersing tetraethyl orthosilicate in a mixture of ethanol and water in a reactor, heating to 40-50°C, slowly stirring and hydrolyzing at 50-100rpm in the reactor for 1-2h to obtain a hydrolyzate, then adding water, adding inorganic fibers and nano-two-dimensional flaky inorganic substances to the reactor, and stirring at 400-800rpm for 15-45min; reducing the stirring speed to 50-100rpm, adding ammonia water to adjust the pH value to 8-9, stirring and reacting for 1-2h, standing for 30-45min, directly extracting the upper clear liquid from the reactor, heating the obtained lower layer to 80°C and drying it to a water content of 15-20%, and then sending it to a fluidized bed dryer, and drying it under hot air suspension to obtain inorganic fibers modified with nano-two-dimensional flaky inorganic substances;

[0012] S2: dissolving polystyrene in toluene to obtain a polymer solution, immersing the inorganic fiber modified with the nanometer two-dimensional flaky inorganic substance obtained in step S1 in the polymer solution, vacuum treating for 3-5 minutes, then filtering to remove the polymer solution, and drying the filtrate at 60-80° C. to remove toluene, thereby obtaining the pretreated inorganic fiber modified with the nanometer two-dimensional flaky inorganic substance;

[0013] S3: Add the inorganic fiber modified with the pretreated nano two-dimensional flaky inorganic material obtained in S2, matrix resin, toughening agent, lubricant, compatibilizer and antioxidant into a high-speed mixer, control the temperature of the high-speed mixer at 120-125°C, perform high-speed dispersion mixing for 30-60 minutes, extrude through a twin-screw extruder, draw strands and cut into pellets to obtain a lubricating inorganic fiber reinforced plastic masterbatch.

[0014] Inorganic fibers with high aspect ratios have obvious reinforcing functions for plastics. In order to use inorganic fibers in the form of preparing reinforced plastic masterbatches, the preferred inorganic fibers have a diameter of 1-10 μm and an aspect ratio of 10-50. Too low an aspect ratio will affect the reinforcing effect, while too high an aspect ratio will affect the dispersibility and even cause fiber removal in the product.

[0015] Further preferably, the inorganic fiber in step S1 is selected from currently known inorganic fibers, including one or more of glass fiber, magnesium hydroxide fiber, wollastonite fiber, calcium carbonate whisker, potassium titanate whisker, calcium sulfate whisker, magnesium sulfate whisker, silicon carbide whisker, aluminum borate whisker, and carbon fiber.

[0016] Preferably, the nano two-dimensional flaky inorganic material in step S1 is selected from at least one of flaky molybdenum disulfide, sericite powder, and graphite, and its D50 thickness is less than 50 nm.

[0017] In order to maintain good fluidity and dispersibility in the processing and use of inorganic fiber reinforced plastic masterbatch, the present invention adheres the nano two-dimensional flaky inorganic substance to the inorganic fiber, and by modifying the inorganic fiber, the good sliding property of the nano two-dimensional flaky inorganic substance is used to give the inorganic fiber excellent sliding property and dispersibility, so that when the inorganic fiber is used to prepare the masterbatch, less lubricant is added and still has good fluidity. In order to adhere the nano two-dimensional flaky inorganic substance to the inorganic fiber, the present invention utilizes the bonding effect of ethyl orthosilicate hydrolyzed into sol to adhere the nano two-dimensional flaky inorganic substance to the inorganic fiber.

[0018] Preferably, the mixed solution of tetraethyl orthosilicate, ethanol and water in step S1 is mixed in a volume ratio of 1:5; wherein the mixing volume ratio of ethanol and water is 5:1.

[0019] Preferably, the amount of water added in step S1 is 1-2 times the volume of the hydrolyzate; the purpose of adding water is to dilute the hydrolyzate, which is beneficial to the dispersion of inorganic fibers and nano-two-dimensional flaky inorganic substances. The present invention utilizes the bonding effect of hydrolysis into sol to make the nano-two-dimensional flaky inorganic substances adhere to the inorganic fibers, and hydrolysis into sol is used as the bonding effect. Therefore, the amount of silicon dioxide that ultimately plays a bonding role cannot be too large. The added water can dilute the hydrolyzate so that the inorganic fibers and nano-two-dimensional flaky inorganic substances are fully dispersed in the hydrolyzate.

[0020] Preferably, the inorganic fiber and the nano two-dimensional flaky inorganic material are added in a mass ratio of 3:1 in step S1; further preferably, the total amount of the inorganic fiber and the nano two-dimensional flaky inorganic material added is 20-25% of the mass of the hydrolyzate after water is added.

[0021] Preferably, the fluidized bed dryer in step S1 is a vibrating fluidized bed dryer, which is fluidized by the dual effects of mechanical vibration and perforated hot air flow, and moves forward under the action of vibration. The material jumps forward under the action of the exciting force in a given direction, and at the same time, the 90-100°C hot air input under the bed fluidizes the material, and the material is fully in contact with the hot air, thereby achieving the effect of drying and dispersing, and preventing the material from excessively sticking during drying. Furthermore, in order to prevent agglomeration due to adhesion, the material is pre-dried to a moisture content of 15-20% before drying.

[0022] Preferably, in step S2, the polystyrene and toluene are dissolved in a mass ratio of 1:8 to obtain a polymer solution. The polymer solution is prepared by dissolving polystyrene in toluene, and the inorganic fiber modified by the nano two-dimensional inorganic sheet is immersed in the polymer solution so that the fiber is impregnated with the polymer, similar to the currently commonly used pre-impregnation treatment of continuous fibers, which is conducive to the compatibility of the inorganic fiber modified by the nano two-dimensional inorganic sheet with the matrix resin.

[0023] Preferably, the vacuum treatment in step S2 is performed for 3-5 minutes, and the vacuum degree used is 0.06-0.08 MPa. Through the vacuum treatment, the polymer solution is fully adsorbed in the gaps of the inorganic fibers modified by the nano-two-dimensional inorganic flakes.

[0024] Preferably, the mixing ratio of the pretreated inorganic fiber modified with nano two-dimensional flaky inorganic material, matrix resin, toughening agent, lubricant, compatibilizer and antioxidant in step S3 is 50-60 parts by weight of the pretreated inorganic fiber modified with nano two-dimensional flaky inorganic material, 30-40 parts by weight of the matrix resin, 1-3 parts by weight of the toughening agent, 0.1-0.3 parts by weight of the lubricant, 3-5 parts by weight of the compatibilizer and 0.1-0.5 parts by weight of the antioxidant.

[0025] Further preferably, the base resin in step S3 is selected from at least one of polypropylene, polyethylene, and polystyrene; the toughening agent is selected from at least one of SBS and POE; the lubricant is selected from at least one of paraffin, polyethylene wax, stearic acid, and ethylenebisfatty acid amide; the maleic anhydride grafted polyethylene and maleic anhydride grafted polypropylene are selected from at least one; the antioxidant is selected from at least one of antioxidant 1010, antioxidant 168, and antioxidant 2246.

[0026] Preferably, the twin-screw extruder in step S3 is a co-rotating twin-screw extruder, the screw aspect ratio is controlled at 25 / 1-35 / 1; the screw speed is controlled at 150-200 rpm; and the extrusion temperature of the twin-screw extruder is controlled at 180-200°C.

[0027] The present invention also provides a lubricating inorganic fiber reinforced plastic masterbatch prepared by the above method. It is well known in the field of polymer materials that the dispersibility of inorganic fibers used to enhance plastics is crucial. Therefore, in the process of preparing plastic reinforced masterbatch, it is necessary to add a relatively high amount of lubricants and dispersants. However, these lubricants and dispersants will affect the strength of the final plastic product. Based on this, the present invention uses the sliding property of the nano two-dimensional sliding flaky inorganic material to adhere and modify the inorganic fiber, and uses the sliding property of the nano two-dimensional flaky inorganic material to give the inorganic fiber good sliding property, so that the amount of lubricating aids such as paraffin is reduced in the preparation process of the reinforced plastic masterbatch, thereby reducing the impact on the rigidity and strength of the product. Using the adhesive property of the silica sol prepared by hydrolysis, the nano two-dimensional sliding flaky inorganic material is adhered and modified to the inorganic fiber, and further treated with a polystyrene solution, the nano two-dimensional sliding flaky inorganic material is adhered and modified to the inorganic fiber to adsorb the polymer at the interface defects, which is beneficial for the inorganic fiber to be compatible and dispersed with the polymer during the processing, preparation and use of the reinforced plastic masterbatch. A more typical advantage is that the nano two-dimensional sliding inorganic material is combined with the inorganic fiber in the form of interface modification in the screw extruder, and has good sliding and dispersibility with the matrix plastic. The resulting reinforced plastic masterbatch used for injection molding plastic products has high strength and high rigidity, and the surface of the plastic product is smooth, which effectively prevents the problem of fiber stripping when used in plastic products.

[0028] A lubricating inorganic fiber reinforced plastic masterbatch and preparation method thereof, compared with the current method of directly using inorganic fiber, matrix resin and lubricant to prepare reinforced plastic masterbatch, the excellent effects of the present invention are embodied in:

[0029] (I) The present invention modifies inorganic fibers by adhering nano-sized two-dimensional sliding flaky inorganic materials, and uses the sliding property of the nano-sized two-dimensional flaky inorganic materials to give the inorganic fibers good sliding properties, thereby reducing the amount of lubricating additives such as paraffin wax used in the preparation process of reinforced plastic masterbatches, thereby preventing the lubricant from affecting the stiffness and strength of the plastic products.

[0030] (ii) Different from directly dispersing nano two-dimensional flaky inorganic materials and inorganic fibers with matrix resin to prepare reinforced plastic masterbatch, the present invention utilizes the adhesiveness of silica sol to adhere nano two-dimensional flaky inorganic materials to modify inorganic fibers, so that the reinforced plastic masterbatch has good fluidity during preparation and use, reduces screw shear damage to fibers, and gives plastic products good rigidity and gloss without fiber loss.

[0031] (III) The preparation method of the present invention adopts mature equipment, the process is easy to control, and it is easy to promote and use on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The beneficial effects of the present invention are further described below in conjunction with the accompanying drawings:

[0033] Figure 1 This is a picture of the inorganic fiber reinforced plastic masterbatch obtained in an embodiment of the present invention, and the surface of the masterbatch is round and smooth.

[0034] Figure 2 This is a picture of the inorganic fiber reinforced plastic masterbatch obtained in Example 1. The surface of the masterbatch is rough and there is fiber loss. DETAILED DESCRIPTION

[0035] The present invention is further described below by specific implementation methods. The following examples are preferred and specific implementation methods of the present invention, but the implementation methods of the present invention are not limited to the following examples.

[0036] Example 1

[0037] S1: In a reactor, 5L of tetraethyl orthosilicate is dispersed in a mixture of 25L of ethanol and water, the temperature is raised to 50°C, and the mixture is slowly stirred at 100rpm for hydrolysis for 2h to obtain a hydrolyzate, and then 40L of water is added, 12kg of glass fiber with a diameter of 1-10μm and an aspect ratio of 10-50 and 4kg of sericite powder with a D50 thickness of less than 50nm are added to the reactor, and the mixture is stirred at 800rpm for 45min; the stirring speed is reduced to 50rpm, and ammonia water is added to adjust the pH value to 9, the mixture is stirred for 2h, and the mixture is left to stand for 45min, the upper clear liquid is directly extracted from the reactor, the lower layer obtained is heated to 80°C and dried to a water content of 20%, and then sent to a vibrating fluidized bed dryer, the material jumps forward under the action of an exciting force in a given direction, and at the same time, the 100°C hot air input from the bottom of the bed makes the material in a fluidized state, the material is fully in contact with the hot air, and is dried under the suspension of the hot air flow to obtain an inorganic fiber modified with a nano-two-dimensional flaky inorganic material;

[0038] S2: dissolving polystyrene and toluene in a mass ratio of 1:8 to obtain a polymer solution, immersing the inorganic fiber modified with the nano two-dimensional flaky inorganic substance obtained in step S1 in an excess of the polymer solution, and vacuum treating the inorganic fiber with a vacuum degree of 0.06 MPa for 5 minutes, so that the polymer solution is fully adsorbed in the gaps of the inorganic fiber modified with the nano two-dimensional flaky inorganic substance, and then filtering to remove the polymer solution, and drying the filtrate at 80° C. to remove the toluene, thereby obtaining the pretreated inorganic fiber modified with the nano two-dimensional flaky inorganic substance;

[0039] S3: 6kg of inorganic fiber modified with pretreated nano-two-dimensional flaky inorganic material obtained in S2, 4kg of polypropylene, 0.3kg of POE8150 (Dow, USA), 0.01kg of polyethylene wax, 0.5kg of maleic anhydride grafted polyethylene, and 0.02kg of antioxidant 1010 were added to a high-speed mixer, the temperature of which was controlled at 125°C, and the high-speed dispersion mixing was carried out at 600rpm for 30min, and then the mixture was sent to a 65-type co-rotating twin-screw extruder with a length-to-diameter ratio of 35 / 1 for extrusion granulation, and the screw speed was controlled at 200rpm; the screw temperature in the feeding zone was controlled at 180°C, the temperature in the mixing zone was controlled at 190°C, and the temperature in the discharging zone was controlled at 200°C, and the pellets were drawn and pelletized to obtain a lubricating inorganic fiber reinforced plastic masterbatch. During the screw extrusion process, the current becomes significantly lower, the material fluidity is better, and the surface of the obtained inorganic fiber reinforced plastic masterbatch is round and smooth, as shown in the attached Figure 1 The figure shows the inorganic fiber reinforced plastic masterbatch obtained by extrusion in Example 1.

[0040] Example 2

[0041] S1: In a reactor, 5 L of tetraethyl orthosilicate is dispersed in a mixture of 25 L of ethanol and water, the temperature is raised to 50°C, and the mixture is slowly stirred at 50 rpm for hydrolysis for 1 h to obtain a hydrolyzate, and then 50 L of water is added, 15 kg of calcium sulfate whiskers with a diameter of 1-10 μm and an aspect ratio of 10-50 and 5 kg of molybdenum disulfide with a D50 thickness of less than 50 nm are added to the reactor, and the mixture is stirred at 500 rpm for 30 min; the stirring speed is reduced to 50 rpm, and ammonia water is added to adjust the pH value to 9, the mixture is stirred for 2 h, and the mixture is left to stand for 45 min, the upper clear liquid is directly extracted from the reactor, the lower layer obtained is heated to 80°C and dried to a water content of 20%, and then sent to a vibrating fluidized bed dryer, the material jumps forward under the action of an exciting force in a given direction, and at the same time, the 100°C hot air input from the bottom of the bed fluidizes the material, the material is fully in contact with the hot air, and is dried under the suspension of the hot air flow to obtain an inorganic fiber modified with a nano-two-dimensional flaky inorganic material;

[0042] S2: dissolving polystyrene and toluene in a mass ratio of 1:8 to obtain a polymer solution, immersing the inorganic fiber modified with the nano two-dimensional flaky inorganic substance obtained in step S1 in an excess of the polymer solution, and vacuum treating the inorganic fiber with a vacuum degree of 0.06 MPa for 5 minutes, so that the polymer solution is fully adsorbed in the gaps of the inorganic fiber modified with the nano two-dimensional flaky inorganic substance, and then filtering to remove the polymer solution, and drying the filtrate at 80° C. to remove the toluene, thereby obtaining the pretreated inorganic fiber modified with the nano two-dimensional flaky inorganic substance;

[0043] S3: 6kg of inorganic fibers modified with pretreated nano two-dimensional flaky inorganic materials obtained in S2, 4kg of polyethylene, 0.1kg of SBS, 0.01kg of ethylenebisfatty acid amide, 0.3kg of maleic anhydride grafted polyethylene as a compatibilizer, and 0.05kg of antioxidant 1010 are added into a high-speed mixer, the temperature of which is controlled at 120°C, and the mixture is dispersed and mixed at a high speed of 600rpm for 30min, and then sent to a 65-type co-rotating twin-screw extruder with a length-to-diameter ratio of 35 / 1 for extrusion and granulation, and the screw speed is controlled at 200rpm; the screw temperature in the feeding zone is controlled at 180°C, the temperature in the mixing zone is controlled at 190°C, the temperature in the discharging zone is controlled at 200°C, and the pellets are drawn and granulated to obtain a lubricating inorganic fiber reinforced plastic masterbatch.

[0044] Example 3

[0045] S1: In a reactor, 5 L of tetraethyl orthosilicate is dispersed in a mixture of 25 L of ethanol and water, the temperature is raised to 50°C, and the mixture is slowly stirred at 50 rpm for hydrolysis for 1 h to obtain a hydrolyzate, and then 50 L of water is added, 15 kg of calcium carbonate whiskers with a diameter of 1-10 μm and an aspect ratio of 10-50 and 5 kg of molybdenum disulfide with a D50 thickness of less than 50 nm are added to the reactor, and the mixture is stirred at 500 rpm for 30 min; the stirring speed is reduced to 50 rpm, and ammonia water is added to adjust the pH value to 9, the mixture is stirred for 2 h, and the mixture is left to stand for 45 min, the upper clear liquid is directly extracted from the reactor, the lower layer obtained is heated to 80°C and dried to a water content of 20%, and then sent to a vibrating fluidized bed dryer, the material jumps forward under the action of an exciting force in a given direction, and at the same time, the 100°C hot air input from the bottom of the bed fluidizes the material, the material is fully in contact with the hot air, and is dried under the suspension of the hot air flow to obtain an inorganic fiber modified with a nano-sized two-dimensional flaky inorganic material;

[0046] S2: dissolving polystyrene and toluene in a mass ratio of 1:8 to obtain a polymer solution, immersing the inorganic fiber modified with the nano two-dimensional flaky inorganic substance obtained in step S1 in an excess of the polymer solution, and vacuum treating the inorganic fiber with a vacuum degree of 0.06 MPa for 5 minutes, so that the polymer solution is fully adsorbed in the gaps of the inorganic fiber modified with the nano two-dimensional flaky inorganic substance, and then filtering to remove the polymer solution, and drying the filtrate at 80° C. to remove the toluene, thereby obtaining the pretreated inorganic fiber modified with the nano two-dimensional flaky inorganic substance;

[0047] S3: Add 5kg of inorganic fibers modified with pretreated nano two-dimensional flaky inorganic materials obtained in S2, 4kg of polyethylene, 0.1kg of SBS, 0.01kg of stearic acid, 0.3kg of maleic anhydride grafted polyethylene as a compatibilizer, and 0.05kg of antioxidant 1010 into a high-speed mixer, the temperature of which is controlled at 120°C, and disperse and mix at a high speed of 600rpm for 30min, and then send them into a 65-type co-rotating twin-screw extruder with a length-to-diameter ratio of 35 / 1 for extrusion and granulation, and the screw speed is controlled at 200rpm; the screw temperature in the feeding zone is controlled at 180°C, the temperature in the mixing zone is controlled at 190°C, the temperature in the discharging zone is controlled at 200°C, and the pellets are cut into strips to obtain a lubricating inorganic fiber reinforced plastic masterbatch.

[0048] Comparative Example 1

[0049] S1: 12 kg of glass fiber with a diameter of 1-10 μm and an aspect ratio of 10-50 and 4 kg of sericite powder with a D50 thickness of less than 50 nm are mixed evenly to obtain a nano two-dimensional flaky inorganic material-inorganic fiber;

[0050] S2: Add 6kg of nano two-dimensional flaky inorganic material-inorganic fiber obtained in S1, 4kg of polypropylene, 0.3kg of POE8150 (Dow, USA), 0.01kg of polyethylene wax, 0.5kg of maleic anhydride grafted polyethylene, and 0.02kg of antioxidant 1010 into a high-speed mixer, the temperature of the high-speed mixer is controlled at 125°C, and high-speed dispersion mixing is carried out at 600rpm for 30min, and then sent to a 65-type co-rotating twin-screw extruder with a length-to-diameter ratio of 35 / 1 for extrusion granulation, and the screw speed is controlled at 200rpm; the screw temperature in the feeding zone is controlled at 180°C, the temperature in the mixing zone is controlled at 190°C, and the temperature in the discharging zone is controlled at 200°C, and the pellets are cut into strips to obtain a lubricating inorganic fiber reinforced plastic masterbatch.

[0051] During the extrusion granulation experiment of this scheme, the nano two-dimensional flaky inorganic material and the inorganic fiber were not pre-treated with silica sol for adhesion, and the nano two-dimensional flaky inorganic material failed to adhere to and cover the inorganic fiber. Instead, the nano two-dimensional flaky inorganic material and the inorganic fiber were directly composited. Since the nano two-dimensional flaky inorganic material failed to effectively adhere to the inorganic fiber, the fluidity of the inorganic fiber was poor during extrusion granulation in the matrix resin, and the dispersion of the inorganic fiber was affected. The gloss of the obtained reinforced plastic masterbatch was significantly deteriorated, which had a certain impact on the reinforcement; if the attached Figure 2 As shown, the surface of the inorganic fiber reinforced plastic masterbatch is rough and there is defibration.

[0052] Comparative Example 2

[0053] S1: In a reactor, 5 L of tetraethyl orthosilicate is dispersed in a mixture of 25 L of ethanol and water, the temperature is raised to 50°C, and the mixture is slowly stirred at 50 rpm for hydrolysis for 1 h to obtain a hydrolyzate, and then 50 L of water is added, 15 kg of calcium sulfate whiskers with a diameter of 1-10 μm and an aspect ratio of 10-50 and 5 kg of molybdenum disulfide with a D50 thickness of less than 50 nm are added to the reactor, and the mixture is stirred at 500 rpm for 30 min; the stirring speed is reduced to 50 rpm, and ammonia water is added to adjust the pH value to 9, the mixture is stirred for 2 h, and the mixture is left to stand for 45 min, the upper clear liquid is directly extracted from the reactor, the lower layer obtained is heated to 80°C and dried to a water content of 20%, and then sent to a vibrating fluidized bed dryer, the material jumps forward under the action of an exciting force in a given direction, and at the same time, the 100°C hot air input from the bottom of the bed fluidizes the material, the material is fully in contact with the hot air, and is dried under the suspension of the hot air flow to obtain an inorganic fiber modified with a nano-two-dimensional flaky inorganic material;

[0054] S2: 6 kg of inorganic fibers modified with nano two-dimensional flaky inorganic materials obtained in S1, 4 kg of polyethylene, 0.1 kg of SBS, 0.01 kg of ethylenebisfatty acid amide, 0.3 kg of maleic anhydride grafted polyethylene as a compatibilizer, and 0.05 kg of antioxidant 1010 are added into a high-speed mixer, the temperature of which is controlled at 120°C, and the mixture is dispersed and mixed at a high speed of 600 rpm for 30 min. The mixture is then sent to a 65-type co-rotating twin-screw extruder with a length-to-diameter ratio of 35 / 1 for extrusion and granulation, and the screw speed is controlled at 200 rpm. The screw temperature in the feeding zone is controlled at 180°C, the temperature in the mixing zone is controlled at 190°C, the temperature in the discharging zone is controlled at 200°C, and the pellets are cut into strips to obtain a lubricating inorganic fiber reinforced plastic masterbatch.

[0055] During the extrusion granulation experiment of this scheme, the inorganic fibers modified by the nano two-dimensional flaky inorganic material were not treated by polymer solution impregnation. The compatibility of the inorganic fibers modified by the nano two-dimensional flaky inorganic material with the matrix resin had certain defects, resulting in limited strength improvement of the obtained inorganic fiber reinforced plastic masterbatch when used to reinforce plastic products.

[0056] Comparative Example 3

[0057] S1: dissolving polystyrene and toluene in a mass ratio of 1:8 to obtain a polymer solution, immersing calcium carbonate whiskers with a diameter of 1-10 μm and an aspect ratio of 10-50 in excess polymer solution, and vacuum treating for 5 min at a vacuum degree of 0.06 MPa to allow the polymer solution to be fully adsorbed, then filtering to remove the polymer solution, and drying the filtrate at 80° C. to remove toluene to obtain pretreated inorganic fibers;

[0058] S2: 5 kg of pretreated inorganic fiber obtained in S1, 4 kg of polyethylene, 0.1 kg of SBS, 0.01 kg of stearic acid, 0.3 kg of maleic anhydride grafted polyethylene as a compatibilizer, and 0.05 kg of antioxidant 1010 are added into a high-speed mixer, the temperature of the high-speed mixer is controlled at 120°C, and high-speed dispersion mixing is performed at 600 rpm for 30 minutes, and then sent to a 65-type co-rotating twin-screw extruder with a length-to-diameter ratio of 35 / 1 for extrusion granulation, and the screw speed is controlled at 200 rpm; the screw temperature in the feeding zone is controlled at 180°C, the temperature in the mixing zone is controlled at 190°C, and the temperature in the discharging zone is controlled at 200°C, and the strands are cut into pellets to obtain a lubricating inorganic fiber reinforced plastic masterbatch.

[0059] This solution does not add flaky molybdenum disulfide to treat inorganic fibers. When extrusion granulation is performed, the viscosity is high, which affects the dispersibility, resulting in limited strength improvement of the obtained inorganic fiber reinforced plastic masterbatch when used to reinforce plastic products.

[0060] Comparative Example 4

[0061] S1: dissolving polystyrene and toluene in a mass ratio of 1:8 to obtain a polymer solution, immersing calcium carbonate whiskers with a diameter of 1-10 μm and an aspect ratio of 10-50 in excess polymer solution, and vacuum treating for 5 min at a vacuum degree of 0.06 MPa to allow the polymer solution to be fully adsorbed, then filtering to remove the polymer solution, and drying the filtrate at 80° C. to remove toluene to obtain pretreated inorganic fibers;

[0062] S2: 5 kg of pretreated inorganic fiber obtained in S1, 4 kg of polyethylene, 0.1 kg of SBS, 0.5 kg of stearic acid, 0.3 kg of maleic anhydride grafted polyethylene as a compatibilizer, and 0.05 kg of antioxidant 1010 are added into a high-speed mixer, the temperature of the high-speed mixer is controlled at 120°C, and high-speed dispersion mixing is performed at 600 rpm for 30 minutes, and then sent to a 65-type co-rotating twin-screw extruder with a length-to-diameter ratio of 35 / 1 for extrusion granulation, and the screw speed is controlled at 200 rpm; the screw temperature in the feeding zone is controlled at 180°C, the temperature in the mixing zone is controlled at 190°C, and the temperature in the discharging zone is controlled at 200°C, and the strands are cut into pellets to obtain a lubricating inorganic fiber reinforced plastic masterbatch.

[0063] This solution does not add flaky molybdenum disulfide to treat inorganic fibers. During extrusion granulation, the amount of lubricant stearic acid is increased. Although the fluidity is good and the dispersion of inorganic fibers can be promoted, the strength improvement is limited when the reinforced plastic masterbatch is used to reinforce plastic products. The bending performance is significantly reduced, resulting in reduced rigidity of the plastic products.

[0064] Enhanced lubrication fluidity test of plastic masterbatch:

[0065] The flow properties of inorganic fiber reinforced plastic masterbatch obtained by the experiment of Example 1-3 and Comparative Example 1-4 were tested with reference to GB / T 3682-2000 "Determination of mass flow rate and melt volume flow rate of thermoplastic plastic melt". The test principle is: the obtained reinforced plastic masterbatch is heated and loaded, so as to measure the mass of the material melt flowing out of the die of specified diameter within 10 minutes to judge the lubrication fluidity. The more material flowing out of the die within 10 minutes, the better the lubrication fluidity. The test conditions are: pressure 2.16kg, temperature 220℃, discharge port diameter Φ2.095mm, pressure piston rod head diameter 9.475mm. The test data are shown in Table 1.

[0066] Table 1:

[0067]

[0068] Reinforced plastic masterbatch is used to enhance the mechanical properties of HDPE:

[0069] The inorganic fiber reinforced plastic masterbatch obtained in Examples 1-3 and Comparative Examples 1-4 was uniformly mixed with 3000J injection molding grade HDPE at a mass ratio of 1:3, and injection molded specimens were tested at 220°C. Pure 3000J HDPE injection molded specimens were used as reference samples.

[0070] The test was carried out according to GB / T 1040 "Test Method for Tensile Properties of Plastics". The injection molded sample was type 1, with a total length of 15 cm, a test parallel width of 1 cm, and a thickness of 0.4 cm, for the tensile strength test. The test results are shown in Table 2.

[0071] In accordance with GB / T 9341-2000 "Test Method for Bending Properties of Plastics", a sample with a length of 8 cm, a width of 1 cm, and a thickness of 0.4 cm was obtained by injection molding. The maximum stress that the sample was subjected to when bent at a test speed of 10 mm / min was used as a characterization of the bending resistance; the greater the bending strength, the better the rigidity of the material. The test results are shown in Table 2.

[0072] Table 2:

[0073]

[0074] Through the above tests, the present invention uses the sliding property of the nano two-dimensional flaky inorganic material to modify the inorganic fiber, and uses the sliding property of the nano two-dimensional flaky inorganic material to give the inorganic fiber good sliding property, so that the amount of lubricating additives such as paraffin is reduced in the preparation process of the reinforced plastic masterbatch. Different from the comparative example 1 in which the nano two-dimensional flaky inorganic material and the inorganic fiber are directly dispersed with the matrix resin to prepare the reinforced plastic masterbatch, the present invention uses the adhesive property of the silica sol to adhere the nano two-dimensional flaky inorganic material to modify the inorganic fiber, so that the reinforced plastic masterbatch has good fluidity during preparation and use, reduces the shear damage of the screw to the fiber, and gives the plastic product good bending resistance and strength, which manifests as good rigidity and gloss.

[0075] It should be understood that the exemplary embodiments described herein should be considered illustrative rather than restrictive. Moreover, the description of each feature or aspect in each embodiment should be applicable to other similar features or aspects in other embodiments.

[0076] Although one or more embodiments of the present invention have been described with reference to the accompanying drawings, it will be understood by those skilled in the art that various changes in form and details may be made therein without departing from the spirit and scope of the invention as defined by the following claims.

Claims

1. A method for preparing a lubricating inorganic fiber reinforced plastic masterbatch, characterized in that: The specific preparation method is as follows: S1: dispersing tetraethyl orthosilicate in a mixture of ethanol and water in a reactor, heating the mixture to 40-50°C, slowly stirring and hydrolyzing the mixture at 50-100rpm in the reactor for 1-2h to obtain a hydrolyzate, then adding water, adding inorganic fibers and nanometer two-dimensional flaky inorganic substances to the reactor, and stirring the mixture at 400-800rpm for 15-45min; reducing the stirring speed to 50-100rpm, adding ammonia water to adjust the pH value to 8-9, stirring the mixture for 1-2h, and letting it stand for 30-45min, directly extracting the upper clear liquid from the reactor, heating the obtained lower layer to 80°C and drying the obtained lower layer to a water content of 15-20%, and then feeding the obtained lower layer into a fluidized bed dryer, and drying the obtained lower layer in a hot air flow suspension to obtain inorganic fibers modified with nanometer two-dimensional flaky inorganic substances; the nanometer two-dimensional flaky inorganic substances have a D50 thickness of less than 50nm; the nanometer two-dimensional flaky inorganic substances are selected from at least one of molybdenum disulfide, sericite powder, and graphite; S2: dissolving polystyrene in toluene to obtain a polymer solution, immersing the inorganic fiber modified with the nanometer two-dimensional flaky inorganic substance obtained in step S1 in the polymer solution, and vacuum treating for 3-5 minutes, with a vacuum degree of 0.06-0.08 MPa; then filtering to remove the polymer solution, drying the filtrate at 60-80° C. to remove toluene, and obtaining the pretreated inorganic fiber modified with the nanometer two-dimensional flaky inorganic substance; S3: Add the inorganic fiber modified with the pretreated nano two-dimensional flaky inorganic material obtained in S2, matrix resin, toughening agent, lubricant, compatibilizer and antioxidant into a high-speed mixer, control the temperature of the high-speed mixer at 120-125°C, perform high-speed dispersion mixing for 30-60 minutes, extrude through a twin-screw extruder, draw strands and cut into pellets to obtain a lubricating inorganic fiber reinforced plastic masterbatch.

2. The method for preparing a lubricating inorganic fiber reinforced plastic masterbatch according to claim 1, characterized in that: The inorganic fiber in step S1 is selected from inorganic fibers with a diameter of 1-10 μm and an aspect ratio of 10-50; the inorganic fiber is selected from one or more of glass fiber, magnesium hydroxide fiber, wollastonite fiber, calcium carbonate whisker, potassium titanate whisker, calcium sulfate whisker, magnesium sulfate whisker, silicon carbide whisker, aluminum borate whisker, and carbon fiber.

3. The method for preparing a lubricating inorganic fiber reinforced plastic masterbatch according to claim 1, characterized in that: In step S1, the mixed solution of tetraethyl orthosilicate, ethanol and water is mixed in a volume ratio of 1:5; wherein the mixed volume ratio of ethanol to water is 5:

1.

4. The method for preparing a lubricating inorganic fiber reinforced plastic masterbatch according to claim 1, characterized in that: The amount of water added in step S1 is 1-2 times the volume of the hydrolyzate.

5. The method for preparing a lubricating inorganic fiber reinforced plastic masterbatch according to claim 1, characterized in that: The inorganic fibers and the nano-sized two-dimensional flaky inorganic substances are added in a mass ratio of 3:1 in step S1; the total amount of the inorganic fibers and the nano-sized two-dimensional flaky inorganic substances added is 20-25% of the mass of the hydrolyzate after water is added.

6. The method for preparing a lubricating inorganic fiber reinforced plastic masterbatch according to claim 1, characterized in that: The fluidized bed dryer in step S1 is a vibrating fluidized bed dryer.

7. The method for preparing a lubricating inorganic fiber reinforced plastic masterbatch according to claim 1, characterized in that: The mixing ratio of the pretreated inorganic fiber modified with nano two-dimensional flaky inorganic material, matrix resin, toughening agent, lubricant, compatibilizer and antioxidant in step S3 is 50-60 parts by weight of the pretreated inorganic fiber modified with nano two-dimensional flaky inorganic material, 30-40 parts by weight of the matrix resin, 1-3 parts by weight of the toughening agent, 0.1-0.3 parts by weight of the lubricant, 3-5 parts by weight of the compatibilizer and 0.1-0.5 parts by weight of the antioxidant; the matrix resin is selected from at least one of polypropylene, polyethylene and polystyrene; the toughening agent is selected from at least one of SBS and POE; the lubricant is selected from at least one of paraffin, polyethylene wax, stearic acid and ethylenebisfatty acid amide; the compatibilizer is selected from at least one of maleic anhydride grafted polyethylene and maleic anhydride grafted polypropylene; the antioxidant is selected from at least one of antioxidant 1010, antioxidant 168 and antioxidant 2246.

8. The method for preparing a lubricating inorganic fiber reinforced plastic masterbatch according to claim 1, characterized in that: The twin-screw extruder in step S3 is a co-rotating twin-screw extruder, the screw aspect ratio is controlled at 25 / 1-35 / 1; the screw speed is controlled at 150-200 rpm; and the extrusion temperature of the twin-screw extruder is controlled at 180-200°C.

9. A lubricating inorganic fiber reinforced plastic masterbatch, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.